Determinación in vitro del efecto antibacteriano de un extracto obtenido de quebracho colorado, Schinopsis lorentzii - Prosdócimo, F. (2010)
Lately, the search for natural growth promoters to replace antibiotics, restricted by internationals regulations, has increased. The in vitro inhibitory activity of a red quebracho extract (Schinopsisi lorentzii) composed of polyphenols over some pathogenic bacteria was determined, comparing it to Bacitracin Methylene Disalicylate at 11 %. Of the fi rst one, doses of 500 ppm up to 0,05 ppm in increasing dilutions were tested. The Bacitracin was used of 330 ppm up to 0,03 ppm. The method of diffusion in agar, modifi ed by Vignolo et al, was applied on Salmonella gallinarum, Escherichi coli, Clostridium perfrigens and Staphylococcus aureus. The extract, as well as the Bacitracin, acted against Gram negative and Gram positive bacteria in various concentrations. These data lead us to suppose that polyphenols may become a tool to substitute antibiotic growth promoters, providing a natural product, safe for human health.